Algunas reflexiones sobre la regulación en el ordenamiento jurídico español de los créditos tributarios en el proceso concursal - Carreras Manero, Olga (Revista de Derecho, 2019)
The purpose of the present paper is to analyse the regulation that Spanish Law providesto tax credits within an insolvency proceeding. In this respect, in first place an studyof the effects and limits of Treasury general priority law will be expounded, secondly,the evaluation of the former within insolvency proceedings will be tackled.
Keywords: General priority law; insolvency proceeding; tax credits priviledges